2019
DOI: 10.1371/journal.pone.0222406
|View full text |Cite
|
Sign up to set email alerts
|

Development of a denoising convolutional neural network-based algorithm for metal artifact reduction in digital tomosynthesis for arthroplasty: A phantom study

Abstract: The present study aimed to develop a denoising convolutional neural network metal artifact reduction hybrid reconstruction (DnCNN-MARHR) algorithm for decreasing metal objects in digital tomosynthesis (DT) for arthroplasty by using projection data. For metal artifact reduction (MAR), we implemented a DnCNN-MARHR algorithm based on a training network (mini-batch stochastic gradient descent algorithm with momentum) to estimate the residual reference (140 keV virtual monochromatic [VM]) and object (70 kV with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The usefulness of image quality improvement for reducing noise and metal artifacts in DT using deep learning has recently been reported [ 4 , 31 ]. Although noise and radiation-dose reductions using deep learning in the DT of the breast are possible, no studies have reported on the reduction of radiation dose related to MAR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The usefulness of image quality improvement for reducing noise and metal artifacts in DT using deep learning has recently been reported [ 4 , 31 ]. Although noise and radiation-dose reductions using deep learning in the DT of the breast are possible, no studies have reported on the reduction of radiation dose related to MAR.…”
Section: Discussionmentioning
confidence: 99%
“…A metal object can produce beam hardening, partial volume, aliasing, small-angle scatter, under-range data acquisition electrons, or overflow of the dynamic range in the reconstruction process. A previous study on digital tomosynthesis (DT) proposed several artifact compensation approaches to minimizing metal artifacts [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be attributed to the lack of new networks for extracting important features from training images, which is a result of the small amount of noise variation data used in training them [18,19]. In previous studies, the reconstruction of the learning mechanism for a specific purpose was achieved by optimizing the learning model by transfer learning [20][21][22].…”
Section: Discussionmentioning
confidence: 99%